Lean Maintenance : Reduce Costs, Improve Quality, and Increase Market Share. - Smith, Ricky (Life Cycle Engineering Ser., 2004)
What is "Lean?" Whether referring to manufacturing operations or maintenance, lean is about doing more with less: less effort, less space, fewer defects, less throughput time, lower volume requirements, less capital for a given level of output, etc. The need to provide the customer more value with less waste is a necessity for any firm wanting to stay in business, especially in today's increasingly global market place. And this is what lean thinking is all about. Lean Operations are difficult to sustain. More Lean Manufacturing Plant Transformations have been abandoned than have achieved true L.